Psychometric properties and cultural adaptation of the Polish Version of the Gay Affirmative Practice Scale - Karniej, Piotr; Dissen, Anthony; Juárez-Vela, Raúl; Santolalla-Arnedo, Iván; Sufrate-Sorzano, Teresa; Garrote-Camara, Maria Elena; Czapla, Michał (Frontiers in Public Health, 2024)
Introduction. The lesbian, gay, bisexual, and transgender (LGBT) people often face unique medical disparities, including obstacles to accessing adequate and respectful care. The purpose of this study was to test the psychometric properties (internal consistency, reliability, and factor structure) of the Polish-language version of The Gay Affirmative Practice Scale (GAP-PL).Material. The study was conducted over a six-month period in 2023, from February to June, involving 329 medical students and professionals who evaluated the GAP-PL.Methods. Before testing the psychometric properties of the original Gay Affirmative Practice Scale (GAP), it was translated and adapted from the original English language version into the Polish language. Authors then tested the psychometric properties of the tool on a sample of 329 participants. The internal coherence of the questionnaire was tested with the analysis of verifying factors (Confirmatory Factor Analysis). Cronbach alpha and the discriminatory power index were used as internal consistency measures.Results. There were more female than male participants (55.32%). More than 53% of the participants were heterosexual, and the average age of the respondents was approximately 30 years. The internal consistency of the Polish-language version and its domains was strong with the overall Cronbach's alpha ranges for each subscale domains ranging between 0.936-0.949. The McDonald's omega coefficient was 0.963.The GAP-PL has excellent properties of factorial validity and can be used in research and clinical practice in Polish-speaking populations.